The Future of Large-Scale Distributed Systems: Trends, Challenges, and Opportunities - Aravind Sekar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Distributed systems form the backbone of our modern digital infrastructure, powering everything from global financial transactions to streaming services and real-time communications. As these systems evolve from simple client-server architectures to complex interconnected components spanning multiple geographic regions, they face transformative trends and significant challenges. Edge computing, serverless architectures, AI-driven operations, data mesh principles, chaos engineering, and sustainability initiatives are reshaping how distributed systems are designed and operated. Meanwhile, organizations must navigate expanding security concerns, complex regulatory requirements, growing operational complexity, and interoperability challenges. This article explores the future landscape of large-scale distributed systems, offering insights into how forward-thinking organizations can leverage emerging patterns and technologies to deliver more responsive, reliable, and efficient services while maintaining security and environmental responsibility in an increasingly connected world.